STUDYING THE COMPOSITION AND PROPERTIES OF USTYURT GYPSUM MINERALS OF THE REPUBLIC OF KARAKALPAKSTAN (Spectrum Journal of Innovation, Reforms and Development, 2024)
This article is dedicated to the study of the chemical and physicochemical properties of gypsum minerals obtained from the gypsum deposits of the Ustyurt Plateau in the Republic of Karakalpakstan. The research focuses on exploring the potential applications of these gypsum minerals as high-quality raw materials in the industrial and construction sectors. During the study, energy dispersive X-ray fluorescence (EDRF) spectrometry, infrared (IR) spectroscopy, and thermal analysis techniques were employed to thoroughly investigate the composition and properties of the samples. The results demonstrate the purity and chemical stability of the gypsum, providing scientific insights into its dehydration and decomposition processes.2